Tradycje krytycyzmu i dogmatyzmu - Drozdowicz, Zbigniew (Polska Akademia Nauk - "Nauka", 2008)
The issue of criticism and dogmatism is one of those problems which various sciences contended with in the past and which is difficult to deal with today. It may seem that criticism and dogmatism are completely mutually exclusive, but the history of sciences shows that in the past they constituted two options mutually exclusive in one respect and complementary in the other. I present here such a mutual exclusiveness and complementarity using examples from the area of philosophy and theology. I am convinced, however, that this situation is also present in other disciplines.
Keywords: criticism; ancient philosophers; medieval theologians; modern scholars; dogmatism; Renaissance theologians; modern philosophers